Sensitization of heat-treated Listeria monocytogenes to added lysozyme in milk. - Kihm, D J (1994)
Listeria monocytogenes was highly resistant to hen egg white lysozyme in whole milk but was sensitive in media and in phosphate buffer. Methods to sensitize the pathogen to lysozyme in milk were investigated. Treatment of whole milk by cation exchange to remove minerals, particularly Ca2+ and Mg2+, slightly promoted inactivation of L. monocytogenes by lysozyme at 4 degrees C over a period of 6 days. Heat treatment (62.5 degrees C for 15 s) strongly sensitized L. monocytogenes to lysozyme in demineralized milk and in MES [2-(N-morpholino)ethanesulfonic acid] buffer. Addition of Ca2+ or Mg2+ to the demineralized milk restored resistance to lysozyme. Cells were more rapidly heat inactivated at 55 degrees C in demineralized milk containing lysozyme, and addition of Ca2+ to the demineralized milk restored the resistance to heat. The results indicate that minerals or mineral-associated components protect L. monocytogenes from inactivation by lysozyme and heat in milk, probably by increasing cell surface stability. The heat treatment of foods containing added lysozyme can probably play a significant role in producing microbiologically safe foods.